Evaluating the preceptor-preceptee relationship among Pharm D students at the King Saud University School of Pharmacy - Mohammed N Al-Arifi (Elsevier, 2018)
Objective: To evaluate preceptee satisfaction concerning preceptorship and the preceptor-preceptee relationship among pharmacy students. Methods: A cross-sectional study was conducted from May 2017 to August 2017 on senior Pharm D students at King Saud University (KSU) College of Pharmacy. A survey instrument was used to get feedback from students regarding their clinical rotations and internships and to evaluate their satisfaction toward preceptorship to meet the goals of the curriculum. Data were entered into SPSS, version 24. Results: Of the 52 students surveyed, 36 (69.2%) were female. More than half of respondents were somewhat satisfied with their preceptors and 11.5% were satisfied. Additionally, only 17% of students rated their preceptors as having excellent clinical teaching skills; about 19% of students rated them as "needs improvement." About 40% of students rated their preceptors as very good, concerned, competent, and safe in their care for persons living with serious co-morbidities and diseases. About half of students (48.1%) rated their non-faculty KSU preceptors' teaching behavior as not satisfactory compared with only four respondents with respect to KSU faculty preceptors' teaching behavior. Conclusion: Pharm D students were somewhat satisfied with their preceptors' teaching behaviors in communication skills, practice, and teaching skills as well as feedback and evaluation to students. To enhance the quality of experiential education, preceptors should be trained to develop programs that direct and energize advancement. Keywords: Assessment, Expectations, Perception, Pharm D student, Pharmacy, Preceptors, Practical experience